The state of the immune system in patients with functional ovarian cysts - Shapoval, O. S.; Vorontsova, L. L. (Modern medical technology, 2022)
Conducting a qualitative and comprehensive examination of patients with functional ovarian cysts is fundamentally necessary to understand the treatment strategy of this pathological state. The objective of the work was to study the features of immune disorders in patients of reproductive age with functional ovarian cysts. Methods. 50 patients of reproductive age with functional ovarian cysts were examined. General clinical, gynecological, ultrasound examination of the pelvic organs, a study of the state of the immune system were carried out. Results. In 70% of patients chronic inflammatory processes of the pelvic organs were detected. The findings revealed varying degrees of immune system disorders in women with ovarian cysts with different parity. In nulliparous and women who gave birth violations of cell immunity of the I degree were revealed, in the group with infertility - II degree. In the group of patients who gave birth and with infertility, the III degree of disorders of humoral immunity was diagnosed, and in nulliparous women - II degree. Conclusion. Determining the degree of disorders of the immune system already at the prehospital stage will allow individualizing the choice and dosing regimen of immunomodulatory drugs as part of the complex therapy of functional ovarian cysts.